HUBUNGAN PERUBAHAN FISIK TERHADAP PREMENTRUAL SYNDROME PADA REMAJA PUTRI - Meri Liandani; Nurma Hidayati (Jurnal Kesehatan, 2023)
Premenstrual syndrome is a collection of physical symptoms, psychology, and lifestyle factors that occur during premenstruation. The purpose of this study was to determine the relationship between physical changes and premenstrual syndrome in female adolescents at SMA Negeri 1 Banjit, Lampung Province in 2020. This type of research used a quantitative method with a cross-sectional approach. In this study the number of samples was 60 class XII students using total sampling technique. Data collection using a questionnaire. Data analysis includes univariate and bivariate analysis. Based on the univariate results, there were (60%) young women who experienced premenstrual syndrome, who experienced physical changes (60%). The results of research data analysis using the chi square test statistical technique at a significant level of 5% (). Bivariate results were obtained with physical changes as a variable (p = 0.002 OR = 7.000). The conclusion is that physical changes are associated with premenstrual syndrome in female adolescents before menstruation. Suggestions, it is necessary to hold counseling on reproductive health programs related to premenstrual syndrome during menstruation, and reproductive health education has been given since class X. Because they really need guidance about premenstrual syndrome.Keywords : Premenstrual Syndrome, Young Women